RISK PREDICTORS IN PERIODONTAL DISEASE - Solomon Sorina Mihaela; Iovan Gianina; Pãsãrin Liliana; Sufaru Irina Georgeta; Mârţu Ioana; Luchian Ionuţ; Mârţu Maria Alexandra; Mârţu Silvia (Romanian Society of Oral Rehabilitation, 2017)
Progress in understanding the etiopathogenesis of periodontal disease has led to a reconsideration of the importance of the role of different risk factors in disease processes. Risk factors act in a very personal way. The same set of risk factors that cause increased susceptibility to periodontitis in a person may have no effect on another person. Changing or eliminating a risk factor (eg smoking cessation) can alter the risk of disease or increase treatment success, whether or not known pathogenic mechanism. Numerous consistent evidence suggests the possible contribution of diabetes, smoking, and stress to periodontal destruction. The exact assessment of the risk factors for any condition depends on the degree of scientific or technical reproducibility and the validity of the diagnostic test used. Recently, attention has been paid to the risk assessment of periodontitis, mainly because the earlier paradigm regarding the etiology and progression of the disease implies an ubiquitous condition - gingivitis, which would lead to periodontitis. Conclusions. The concept of risk is a complex notion in permanent dynamic (risk factors / risk predictors). Dentists should be encouraged to communicate with general practitioners about the health of their patients, and general practitioners should be alerted to the possible risks of severe / aggressive forms of periodontal disease.